Historiography in the Middle Ages - Deliyannis, Deborah Mauskopf, 1966- (Brill, 2003)
A collection of 11 essays describing the writing of history in mediaeval Western Europe. Each chapter examines a type of subject matter about which mediaeval historians wrote, and discusses both the texts and modern approaches to these texts. The authors include historians and literary scholars.